Fungibility and the impact of development assistance : evidence from Vietnam's health sector - Wagstaff, Adam, 1959- 1959- (Policy research working paper, 2008)
"How can the impact of aid be estimated in the presence of fungibility? And how far does fungibility reduce its benefits? These questions are analyzed in a context where a donor wants to target its efforts on a specific sector and specific geographic areas. A traditional differences-in-differences method comparing the change in outcomes between the target and nontarget areas before and after the project risks misestimating the project's benefits. The paper develops an alternative estimation method in which intersectoral fungibility reduces project benefits insofar as government spending has a smaller impact in the sector to which the funds leak than in the target sector, while intrasectoral fungibility reduces benefits insofar as the donor is able to leverage productivity increases in government spending in the target areas. The methods are applied to two contemporaneous World Bank health projects that set out to target assistance on approximately one-half of Vietnam's provinces. Aid is not apparently fungible between Vietnam's health sector and other sectors, but is fungible across provinces within the health sector. Differences-in-differences yield an insignificant impact on infant mortality, while the use of the new method yields a statistically significant impact of around 4 per 1000 live births. The results, however, are ambiguous on the costs associated with intrasectoral fungibility. "--World Bank web site